SOCIETY PARTICIPATION IN VILLAGE SYSTEM OF PEMALANG AREA (SIDEKEM) PEMALANG REGENCY (ICT VOLUNTEERS AND VILLAGE INFORMATION SYSTEM OF PEMALANG AREA) - Dita Fatma Anggraeni; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2018)
Development of technology has been growing into government system. Charge of bureaucracy reformation has brought technology to participate in governance system, especially in public service innovation. Development of technology in Indonesia has not yet distributed well, it is shown by many areas have not aware of technology. Inline with Law Number 6 Year 2014 about Village that said “Village has right to get information access through Village Information System which developed by City/Regency Governance”.The research describe society participation which are ICT Volunteers in helping governance program that is Village System of Pemalang Area (SIDEKEM) in Pemalang Regency. Research’s method is descriptive qualitative and theory being used is individual and society participation theory.Research result shows that ICT Volunteers participation has born from passion and concern of society in development. Through Empowerment Center of Information and Village (PUSPINDES), ICT Volunteers can participate in supporting governance policy. ICT Volunteers participation can be obtain by governance role which is Society and Village Governance Empowerment Body (DINPERMADES). However, there are some obstacles, which are the lack number village governance officer who understand about technology, indiscipline action of village officer in training held by PUSPINDES and lack of awareness village society on the importance of technology. The obstacles can be overcome by appointing village administrators, giving award to villages, ICT Volunteers and DINPERMADES continuously supervising and evaluating as well as giving some innovation in the implementation of SIDEKEM.Keywords: Society Participation, ICT Volunteers, PUSPINDES, DINPERMADES,Innovation, SIDEKEM